Effects of Using Practical Activities in Teaching Electronics Concept to Pre-service Teachers - Amoah, Charles Agyei; Himah, Valentina Osei; Parker, Joseph (International Journal of Scientific Research and Management (IJSRM), 2018)
The study sought to use practical activities to teach basic electronics concepts to pre- service teachers from Atebubu College of Education in Ghana. Action research was used to carry out the investigation. A total of 200 pre-service teachers from first year were conveniently selected for the study. The instruments for the study were achievement test items and questionnaire. The result of the study indicated that the performance of the experimental group was significantly better than the pre-service teachers from the control group. It was recommended that the Principal and the Head of Science Department of Atebubu College of Education should organize workshops, seminars, and in-service training on the effective use of practical activity methods in teaching concept of electronics.